Long-term ocular hypotensive effect of levobunolol: results of a one-year study. Issue 8 (August 1985) - Ober, M; Scharrer, A; David, R; Biedner, B Z; Novack, G D; Lue, J C; Robins, D S; Duzman, E
Abstract : Data for the first 12 months are reported for an ongoing, multicentre, clinical study comparing the long-term, ocular hypotensive efficacy and safety of topical levobunolol (0.5% and 1%) and timolol (0.5%). This study was a double-masked trial testing 88 patients with chronic open angle glaucoma or ocular hypertension. During the 12-month period drops were instilled twice daily into both eyes after a washout of prestudy ocular hypotensive medication. The effect of the three treatments in reducing intraocular pressure (IOP) was similar. Mean IOP reductions over the 12 months averaged 7.2 mmHg for the 0.5% levobunolol group, 6.2 mmHg for the 1% levobunolol group, and 6.0 mmHg for the timolol group. Decreases in mean heart rate of up to 5 beats per minute were observed in the 0.5% levobunolol group, up to 8 beats per minute in the 1% levobunolol group, and up to 4 beats per minute in the timolol group. Several patients were removed from the study owing to side effects possibly related to levobunolol treatment.